Hurricane hunters! : riders on the storm - Demarest, Chris L. (Margaret K. McElderry Books, 2006)
Learn about real life heroes who risk their lives studying hurricanes. It's a sunny, beautiful day on America's Southeastern Coast. But out in the Atlantic Ocean, chaos is brewing. Waves are crashing. Winds are blowing. And the National Hurricane Center is calling the Hurricane Hunters! A special weather reconnaissance squadron of the Air Force, these brave men and women fly their WC-130 Hercules aircraft into the heart of a two-hundred-mile-wide hurricane and collect information: in which direction the hurricane is heading, how fast it's moving, and how big it's growing. Before the end of their twelve-hour flight, the Hurricane Hunters will have gathered enough information to save many lives. Acclaimed author and artist Chris L. Demarest takes you inside the storm with these real-life adventurers who risk their lives to keep our shorelines safe.